2011
DOI: 10.1007/s00125-011-2299-x
|View full text |Cite
|
Sign up to set email alerts
|

An increased frequency of NK cell receptor and HLA-C group 1 combinations in early-onset type 1 diabetes

Abstract: Aims/hypothesis Natural killer (NK) cells serve as primary immune surveillance and are partially regulated by combinations of killer immunoglobulin-like receptor (KIR) genes and their HLA class I ligands. Alterations in NK cell activity have been associated with type 1 diabetes. The aim of this study was to determine whether KIR-HLA class I gene frequency: (1) is altered in a current population with type 1 diabetes compared with healthy controls; and (2) has changed over the half century in which the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…Moreover, some alleles of KIR2DL2 are able to cross‐react, with differing avidities, with a small number of C2 and may used it as a functional ligand that can be responsible for the inhibition of NK cells activation . A previous studies demonstrated that the KIR2DL2, KIR2DS2 and KIR2DL3 genes, which share the HLA‐C1 ligand, are involved in increased susceptibility to several diseases , including malaria . In contrast, similar associations were not observed in our population.…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, some alleles of KIR2DL2 are able to cross‐react, with differing avidities, with a small number of C2 and may used it as a functional ligand that can be responsible for the inhibition of NK cells activation . A previous studies demonstrated that the KIR2DL2, KIR2DS2 and KIR2DL3 genes, which share the HLA‐C1 ligand, are involved in increased susceptibility to several diseases , including malaria . In contrast, similar associations were not observed in our population.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, KIR2DL2 binds HLA-C alleles in the C1 group. Some studies have reported increased T1D risk for KIR2DL2 [103,105,108]. However, in individuals lacking a C1 allele (i.e., both alleles have HLA-C alleles in the C2 group rather than the C1 group), any risk from KIR2DL2 is necessarily absent.…”
Section: Kir Association With T1dmentioning
confidence: 96%
“…The association of KIR genes with many diseases such as leukaemia (De Smith et al, ), T1DM (van der Slik et al, ), idiopathic bronchiectasis (Boyton et al, ), psoriasis vulgaris (Suzuki et al, ), uveitis (Levinson, ), systemic sclerosis (Salim et al, ), systemic lupus erythematosus (Hou, Zhang, & Xu, ), ankylosing spondylitis (Jiao et al, ), rheumatoid arthritis (Majorczyk et al, ) and autoimmune hepatitis (Littera et al, ) was reported. KIR genes have been reported to be associated with T1DM and LADA in several populations (van der Slik et al, ; Tan, Lin, & Huang, ; Mehers et al, ; Zhi et al, ). However, very few reports were available on KIR–HLA association with T2DM (Caselli et al, ; Guo et al, ).…”
Section: Introductionmentioning
confidence: 99%